Kazakh national intelligence and Alash movement at the beginning of XX-th century (Journal of history, 2020)
This article discusses the political program of the party, who opposed the imperial government, as well as the activities and goals of representatives of the national intelligentsia and the formation of the ideas of national statehood in the activities of the Alash movement. The main purpose of this study is a deep analysis of the representatives of the national intelligentsia in the formation of statehood and the revival of the national ideology. At the beginning of XXth century Kazakh intelligence who studied in Russian cities felt Russian culture and political influence upon them and began to develop political ideas and advocate democratic ideas by the influence of some oppositional parties The article also examines the role of representatives of the national intelligentsia in the revival of the national idea and national associations. It is clear that Kazakhstan built its road to independence in the end of XX century. It is very important to know work and point of view of Kazakh intelligence about solving the important problems according to necessary state structures like: territory, national language, national state ideology, mentality, forming of national ideology and democracy. Key words: Kazakh intelligentsia’s activity, Kazakh intellectuals, independence of Kazakhstan, Kazakh nation, Alashorda.